2006
DOI: 10.1371/journal.pgen.0020222
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Determinants of Gene Expression Plasticity by Genetical Genomics in C. elegans

Abstract: Recent genetical genomics studies have provided intimate views on gene regulatory networks. Gene expression variations between genetically different individuals have been mapped to the causal regulatory regions, termed expression quantitative trait loci. Whether the environment-induced plastic response of gene expression also shows heritable difference has not yet been studied. Here we show that differential expression induced by temperatures of 16 °C and 24 °C has a strong genetic component in Caenorhabditis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
273
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(298 citation statements)
references
References 31 publications
23
273
1
1
Order By: Relevance
“…For these distal linkages, 105 out of 107 peaks were found on different chromosomes as the target genes. Results from our previous study (Smirnov et al 2009) and those from model organisms (Li et al 2006;Smith and Kruglyak 2008) have shown that the individual variation in the responses to cellular perturbations is mostly due to polymorphic trans-acting factors.…”
Section: Dna Variants That Affect Radiationinduced Gene Expression Anmentioning
confidence: 86%
“…For these distal linkages, 105 out of 107 peaks were found on different chromosomes as the target genes. Results from our previous study (Smirnov et al 2009) and those from model organisms (Li et al 2006;Smith and Kruglyak 2008) have shown that the individual variation in the responses to cellular perturbations is mostly due to polymorphic trans-acting factors.…”
Section: Dna Variants That Affect Radiationinduced Gene Expression Anmentioning
confidence: 86%
“…Several such panels have been or are being developed for a variety of species, including yeast, Drosophila (Ayroles et al 2009), Arabidopsis (Kover et al 2009), maize (Buckler et al 2009), Caenorhabditis elegans ( Johnson and Wood 1982;Li et al 2006;Rockman and Kruglyak 2009), and mice (Chesler et al 2008;Iraqi et al 2008;Morahan et al 2008). Efforts are also being made to expand (Peirce et al 2004) and maximize the potential of existing populations (Bennett et al 2010).…”
mentioning
confidence: 99%
“…eQTL can be cis-or trans-acting, reflecting local and distant regulation of gene expression, respectively. They have been thoroughly studied in humans, yeast, plants, rats, mice, and worms (Brem et al 2002;Schadt et al 2003;Li et al 2006;Petretto et al 2006;Keurentjes et al 2007;Farber et al 2009). But, as far as we are aware of, all eQTL studies only focused on one time point or age group, whereas most complex traits and diseases such as cancer are age-related.…”
mentioning
confidence: 99%
“…Here we present the first genome-wide study of heritable gene expression regulation as a function of age using a set of 36 single nucleotide polymorphism (SNP)-genotyped recombinant inbred lines (RILs) (Supplemental Table 1) derived from C. elegans wild types N2 and CB4856 (Li et al 2006). The CB4856 3 N2 RIL population displays large genetic and phenotypic differences for a wide range of traits such as reproduction, growth (Gutteling et al 2007;Kammenga et al 2007), gene expression (Li et al 2006), and copulatory plug formation (Palopoli et al 2008), to name a few.…”
mentioning
confidence: 99%
See 1 more Smart Citation